Systematic literature review on indexes aimed at urban sustainability - Yuassa, Vanessa Naomi; Gonçalves, Luciana Márcia; Guerreiro, Thais de Cassia Matinelli (National Journal of City Management, 2025)
Objective – To present a bibliometric study on indexes related to urban sustainability, with an emphasis on identifying the most relevant aspects for their development and application.Methodology – A bibliometric analysis was conducted based on scientific articles available in the Web of Science and Scopus databases, covering the period from 2016 to 2020. The study addressed the structure of indexes considering elements such as dimensions, indicators, methods of selection and normalization, weight assignment, and aggregation techniques.Originality/relevance – The research highlights the challenges involved in operationalizing indexes with more than 50 indicators, due to the lack of reliable data sources and the absence of methodological standardization in the construction of urban sustainability indexes.Results – The main findings indicate the predominance of the traditional sustainability tripod (environmental, social, and economic), with occasional additions of territorial dimensions. There is no consensus regarding the criteria and methods for selecting indicators. In weight assignment, there is a tendency toward objective methods to reduce subjectivity. Regarding aggregation methods, simple calculations are the most commonly used.Theoretical/methodological contributions – The study reveals theoretical and methodological gaps in the definition and application of urban sustainability indexes, pointing to the need for greater rigor and clarity in the processes of indicator construction and methodology validation.Social and environmental contributions – By highlighting the difficulties and limitations of existing indexes, the research contributes to the formulation of more effective and applicable indicators for urban management, with the potential to improve public policies and urban planning practices aimed at sustainability.
Keywords: Index; Urban development; Urban planning; Sustainability